Long-term survival of uveal melanoma patients with respect to clinical, hemodynamic and morphological characteristics of the tumor - S. V. Saakyan; A. G. Amiryan; A. Yu. Tsygankov; M. R. Khlgatyan (Российский офтальмологический журнал)
Purpose. Evaluation of long-term results of uveal melanoma (UM) treatment in patients depending on clinical, hemodynamic and morphological parameters of the tumor.   Material and methods. Long-term results of treatment were analyzed in 394 UM patients aged 17 to 82 (mean age 53.1 ± 13.2). The median follow-up was 56 months. Group A (n = 242, organ-preserving treatment) consisted of patients with a tumor height of 5.0 ± 1.8 mm and base diameter of 12.7 ± 2.9 mm. Group B (n = 152, enucleation) included patients with 8.3 ± 2.8 mm tumor height and 15.2 ± 4.1 mm base diameter. Overall survival and disease-dependent survival were determined.   Results. The cumulative 3-, 5-, and 7-year survival rates of patients with choroidal melanoma were 91.6 ± 1.7, 84.0 ± 2.5, 74.0 ± 3.8 % , and those with ciliochoroidal melanoma were 84.2 ± 5.6, 79.9 ± 5.8, and 53.0 ± 14.7 %, respectively (p = 0.048). In group A, the 5-year survival rates of patients with mushroom-shaped and irregular forms were 80.6 ± 5.9 and 74.6 ± 10.9 %, respectively, and 96.0 ± 2.0 % for dome-shaped UM. The worst 5-year survival rates were shown by patients with tumor stabilization, and the best ones, by patients with complete tumor resorption (x2 = 6.880, p = 0.008). Patients with post-radiation optical neuropathy (n = 193) had better 5-year survival rates (90.3 ± 2.9 %) than patients (n = 49) without neuropathy (77.5 ± 8.0 %). In group B, cumulative 1-year survival was 95.2 ± 1.9 %, 2-year survival, 89.2 ± 2.8 % , 3-year survival, 84.9 ± 2.9 % , 4-year survival, 81.8 ± 3.6 %, 5-year survival, 77.5 ± 4.0 % , 6-year survival, 67.9 ± 4.8 % , and 7-year survival was 64.7 ± 5.2 %. In epithelioid-cell, mixed-cell, and spindle-cell types of UM, the 5-year survival rates were 46.3 ± 12.0, 70.7 ± 8.0 %, and 84.8 ± 5.4 %, respectively (x2 = 11.571, p = 0.004). The 5-year survival rate of patients with extrascleral growth was 56.0 ± 10.4 % and without extrascleral growth it was 81.7 ± 4.0 %.   Conclusion. In organ-preserving treatment, the combination of prognostic factors allows us to stratify the patients based on the risk of early metastasis, which allows for personalized dynamic monitoring, taking into account the vital prognosis of a particular patient.